Prioritised Zoonotic Diseases of Nepal: A Review - Gautam, Anil; Upadhayay, Pramod; Ghimre, Devendra; Khanal, Ashwani; Gaire, Asmita; Kaphle, Krishna (International Journal of Applied Sciences and Biotechnology, 2021)
World Organization for Animal Health (OIE) has estimated that 60% of infectious diseases and 75% of emerging and re-emerging diseases of humans have an animal origin. In Nepal there six zoonoses; Taeniasis/cysticercosis /Neurocysticercosis, Leptospirosis, Hydatidosis, Brucellosis; Toxoplasmosis and Avian Influenza are identified as priorities zoonotic diseases as they are found to have epidemic potential. Although they are prioritised, there is high prevalence of these diseases in both humans and animals with insufficient research and data. Coordination of multiple stakeholders of public and animal health and One Health collaboration are crucial to control and elimination zoonotic diseases in Nepal. Int. J. Appl. Sci. Biotechnol. Vol 9(1): 1-15